Implementation of the Make a Match Learning Model to Improve Learning Outcomes Al-Qur'an Hadith for Students Class VIII MTs. PP Islamic College Ganra District Ganra Soppeng District - Ali Musyafa; Muh. Dahlan; Marhani (Universitas Muhammadiyah Palu, 2024)
This research aims to determine the application of the make a match learning model to improve the learning outcomes of Al-Qur'an Hadith students in class VIII MTs. PP Ganra Islamic College, Ganra District, Soppeng Regency. This research uses a qualitative descriptive model, namely research that intends to understand and explain phenomena about what research subjects experience such as behavior, perceptions, motivations, actions, etc. holistically, and descriptively in the form of words and language in a special natural contexts and by utilizing various natural models. This research shows that the Make A Match learning model applies to the Al-Qur'an Hadith subject in class VIII MTs. PP. Ganra Islamic College has proven effective in increasing student engagement and understanding. Through systematic and cooperative application, this model succeeds in creating a dynamic and participatory learning environment, in accordance with the principles of active learning recommended in modern education. The use of question and answer cards not only facilitates in-depth understanding of the material, but also encourages the development of students' social and collaborative skills. This success shows that teachers at MTs. PP. Ganra Islamic College is able to implement the Make A Match learning model well, as supported by Slavin's cooperative learning theory, thereby making a positive contribution to improving student learning outcomes in Al-Qur'an Hadith subjects.